The new green grabbing frontier and participation: conserving drylands with or without people - Gargallo, E.; Haller, T.; Chatty, D.; Weissman, S.; Meessen, H.; Giger, M.; Maisuradze, R.; Iashvili, N.; Chkhobadze, N. (Drylands facing change: Interventions, investments and identities, 2023)
Drylands have been affected by so-called green grabbing—that is, the dispossession or displacement of local communities in order to expand areas devoted to conservation, as well as the signifcant curtailment of access to natural resources by non-displaced groups (Fairhead et al. 2012). Green grabbing can take different forms, such as the removal of people from offcially protected areas (PAs), the concession of communal lands to outside investors that will develop conservationrelated activities, and the negative side-effects of community conservation (CC) programmes.